Encumbrances To Non-Governmental Organisations (Ngos) Efforts Towards Conflict Resolution In The North West Region Of Cameroon, 1990-2010 - Monteh, René Ngek (Advances in Social Sciences Research Journal, 2021)
Conflicts have existed since the creation of man and have remained an undeniable aspect of the human society. Conflicts have manifested in various ways in Cameroon and the incidence has indeed been high in the North West Region. This study entitled “Challenges of Non-Governmental Organisations in Conflict Resolution in the North West Region, 1990-2010” seeks to examine the difficulties that NGOs involved in conflict resolution faced between 1990 and 2010 in this part of Cameroon. The culture of peace has been difficult to nurture in the region because of the proliferation of conflicts. The present study therefore, seeks to explore the sector of NGOs with special focus on their challenges in conflict management and resolution since many of these NGOs were devoted to human rights issues, capacity building and conflict resolution. A critical study of existing literature on the subject of conflicts and our numerous visits to the field revealed that NGOs in this domain had invested valuable time and resources to prevent the escalation of tension among the antagonist of the region. Despite the influential role and enormous resources deployed by these NGOs, many obstacles perturbed the realisation of their missions. By the end of our research these challenges which constituted the “raison d’être” of the present study turned out to be internal and external.